Enhancing Conceptual Understanding in Elementary Science Learning through the Problem-Based Learning Model: A Literature Review - Irsyad, Kamaludin; Fauziyah, Zumrotul; Ali, Mukti (ISEJ : Indonesian Science Education Journal, 2024)
Problem-Based Learning (PBL) has been widely recognized as an effective pedagogical model for improving students’ understanding of science by encouraging active engagement, critical thinking, and problem-solving. This study aimed to analyze conceptually how the application of PBL can enhance students’ comprehension in natural science learning at the elementary school level. A library research design was employed, drawing upon books, journal articles, and relevant prior studies, which were systematically reviewed and synthesized to examine theoretical foundations, practical implementations, and empirical findings of PBL in science education. The analysis revealed that PBL facilitates higher-order thinking skills by providing authentic problem contexts that require inquiry, collaboration, and reflective learning, thereby improving students’ conceptual mastery and their ability to connect scientific principles with real-life experiences. Furthermore, PBL was shown to strengthen creativity, motivation, communication, and collaboration among learners, making it an appropriate model to prepare students with competencies aligned to 21st-century education. The novelty of this study lies in its contextualization of PBL within Indonesian elementary education, highlighting both its theoretical potential and practical relevance for improving science literacy. The findings imply that educators, curriculum developers, and policymakers should consider integrating PBL as a strategic instructional model to enhance the quality of science teaching and learning, while future studies are encouraged to validate these insights through classroom-based empirical research.